2014
DOI: 10.4236/ojog.2014.410086
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (HBV) Infection in Pregnancy: Knowledge and Practice of Care Providers in Nigeria

Abstract: Purpose: To determine the practice of obstetric care providers regarding routine screening for hepatitis B virus infection, and to assess their knowledge of the management of the positive pregnant women. Methods: A cross sectional descriptive study of obstetric care providers in southwestern Nigeria. Mean and standard deviation was used to summarize continuous variables while frequency and percentage was used for categorical variables. Categorical variables were compared with chi-square test and Fisher's exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Out of the 80% of mothers who received ANC in a study in Nigeria, only 6% of mothers were screened for HBsAg (Sadoh and Eregie, 2014). Some might argue that only those with risk factors should be screened based on costeffectiveness but some studies showed that majority of HBsAg-positive pregnant women in Nigeria had no identifiable risk factor, making routine screening important (Adeyemi et al, 2014;Okusanya et al, 2013).…”
Section: Service Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 80% of mothers who received ANC in a study in Nigeria, only 6% of mothers were screened for HBsAg (Sadoh and Eregie, 2014). Some might argue that only those with risk factors should be screened based on costeffectiveness but some studies showed that majority of HBsAg-positive pregnant women in Nigeria had no identifiable risk factor, making routine screening important (Adeyemi et al, 2014;Okusanya et al, 2013).…”
Section: Service Deliverymentioning
confidence: 99%
“…Studies showed that the knowledge of HBV management among health workers in Nigeria is low as only 32% of health workers were aware of the timing of HB-BD administration (Adeyemi et al, 2014;Nwokediuko, 2011). There are also misconceptions held by health workers concerning use of vaccine vials which lead to many infants missing the HB-BD, despite delivery in the hospital (Sadoh and Sadoh, 2014).…”
Section: Health Workforcementioning
confidence: 99%